Stedman's Medical dictionary - Stedman, Thomas Lathrop (Baltimore : Williams & Wilkins, 1982)
Comprehensive standard medical dictionary. Intended for students and professionals in all the life sciences. Medical entomology section. Includes eponyms and brief, biographical information. 8152 new entries and 25,735 entries revised to reflect expanded knowledge in fields such as immunology, microbial genetics, and molecular biology. 6 appendixes of miscellaneous information. 1st ed., 1911; 23d ed., 1976.
Includes subentry index.
Keywords: Medicine; Dictionary